Pemanfaatan Model Pembelajaran Al- Qashash /Kisah Dalam Al-Qur’an Pada Bahasan Keilmuan - Malik, Amarullah (Program Studi Manajemen Pendidikan Islam, 2023)
Qashash al-Qur'an or stories in the Qur'an that fill a quarter of the Qur'an is believed to be true as a true story revealed by Allah to be taken lessons (ibrah), wisdom and used as a source of role models in everyday life. Some of these stories have been obtained historical evidence through archaeological research, while others have not been proven. There are many ways to explore ibrah from these stories, including; historical approach, philosophy, sociology, psychology and so on. The researcher applied library research as a method to analyzed Ibrah within the Holly Qur’an. The Qur'an is not a scientific book, such as a history book for example, but it can be used as a source of knowledge. This can be seen from the writings of Ibn Khaldun, Haekal, Muhammad al-Ghazali, Sayid Ramadhan al-Buti, Munzir Hitami, Sayyid Qutb, Muhammad Qutb, Komaruddin Hidayat and so on who use the stories in the Qur'an as a source of reference or reference. the inspiration. Unfortunately, the approach taken by some groups in the study of the stories of the Qur'an is more about compiling a history than an in- depth study of ibrah or the lessons that can be drawn from it. Presumably, it is necessary to study the stories of the Qur'an by using various other methods and approaches so that it is more useful for the development of divine civilization on earth.